Modern parasitology [ a textbook of parasitology - Cox, Francis E. G. (Blackwell Scientific Publications, 1993)
This is a thorough revision and update of the highly successful first edition, which which achieved sales in excess of 4,500. The text serves as a comprehensive introduction to parasitology for both undergraduate and beginning graduate students. In this edition, particular emphasis is placed on parasites of human and veterinary importance